Effect of Dexamethasone Administration toward Hematopoietic Stem Cells and Blood Progenitor Cells Expression on BALB/c Mice - Wira Eka Putra; Aris Soewondo; Muhaimin Rifa'i (The Journal of Pure and Applied Chemistry Research, 2015)
Hematopoiesis play important roles on maintaining body homeostasis. Dexamethasone (Dex) known as synthetic glucocorticoids and widely affect many regulations i.e. immune system, inflammation, reproduction and all aspects of metabolism. Generally Dex were used as therapeutic agentsto ameliorate many kind of diseases including cancer and auto-immune diseases. The aims of this research were to investigate the effect of Dex administration toward expression of hematopoietic stem cells and blood progenitor cells. Two weeks old BALB/c mice were used and treated with 3 groups of Dex administration i.e. untreated-mice, 0.5 mg/kg BW, and 10 mg/kg BW. Mice were sacrificed on day-7 after administration of Dex. The bone marrow stromal cells were isolated, then followed by flow cytometry analysis. The result showed that, Dex administration with dose 0.5 mg/kg BW significantly increase the expression of hematopoietic stem cells, CD34+, chemokines, SDF-1+, erythroid progenitor cells, Gr-1-TER-119+, granulocytes, Gr-1+, and B progenitor cells, B220+.